Geoquímica de Elementos Terras Raras e Elementos Traço na Fluorita: Comparação entre Filões das Partes Norte e Sul do Distrito Fluorítico de Santa Catarina e Implicações no Modelo Genético - JELINEK, ANDRÉA RITTER; NETO, ARTUR BASTOS (Pesquisas em Geociências, 2008)
Rare earth elements geochemistry was applied on fluorite from Grão-Pará sub-district, northern Santa Catarina Fluorite District, and compared with southern ore veins data in attempt to identify fluid, REE and F sources. The data suggest different granitic rocks as F sources for southern and northern fluorite and that rare earth elements content in the later was strongly affected by the granitic bodies associated with the Rio dos Bugres shear zone, which is responsible for a distinct Yb/Tb signature. In both sub-districts, F and REE were leached from granites by meteoric fluids. Late Grão-Pará fluorite was deposited under influence of a mixing with halite-saturated saline fluid from the sedimentary cover. When saline fluid became dominant, the fluorite deposition stopped to give place to gorceixite deposition under oxidant conditions.